Peripherally Inserted Central Catheters (PICC): A Promising Technique (Nepalese Journal of Radiology, 2012)
Peripherally Inserted Central Catheters (PICC): a promising technique. To describe technical features and benefits from PICC lines. NJR I VOL 2 I ISSUE 1 64-66 Jan-June, 2012 DOI: http://dx.doi.org/10.3126/njr.v2i1.6986